MANAGEMENT OF BUSINESS PROCESSES OF INTERNATIONAL COMPANIES: CONCEPTUAL AMBUSH, PRINCIPLES, WIKIS - YATSENKO, VICTORIA (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article is devoted to the study of the theoretical foundations of business process management of international companies. The study identifies four areas that use the process approach as the main approach to increase productivity, namely total quality management (TQM), the process of continuous improvement, business process improvement or business process management, business process reengineering (BPR). As part of the key determinants of business process formation, the author highlights business goals, business stages and stakeholders. Based on the theoretical analysis of foreign scholars’ research, five main areas of management philosophy of international companies were identified: 1) business process management system and organizational culture, which is based on the thesis that culture can be defined as a set of common values within a group. Manifested through ideas, attitudes, rituals, technologies, products and institutions; 2) business process management system to support the organization of processes: the business process management system was initially focused on the process organizational approach, which is used to design, analyze and improve business processes to manage and improve organizational behavior. 3) business process management system and organizational efficiency: the measurement system is crucial in management processes to assess and disseminate success stories for motivational purposes, assess progress, allocate and redistribute resources, and implement a system of continuous improvement; 4) business process management system as a tool to support corporate governance: modern international companies tend to adopt strategies that implement positive differentiation in the segments in which they operate, if they want to keep themselves and survive in the market; 5) business process management system as a tool of competitive advantage: the main purpose of business process management system is to create a competitive advantage of the company, thereby ensuring the quality of products and services that satisfy customers better, products and services of competitors.